Komunikasi Persuasif Konten Youtube Kementerian Agama dalam Mengubah Sikap Moderasi Beragama - Fasha Umh Rizky; Nur Syam (Jurnal Ilmu Komunikasi, 2021)
The purpose of this study is to understand how the application of persuasive communication in explaining religious moderation, especially that which is applied to the Youtube content of the Indonesian Ministry of Religion, entitled "why should religious moderation". This research method uses a qualitative approach and a document study method, with the unit of analysis in the form of social artifacts. The results of this study indicate that in one-way communication through this Youtube video content, it is found the use of integration techniques, reward or pay-off techniques, fear-arusing techniques and icing techniques. The use of integration techniques can cause the communicant to feel that they are facing a problem and have the same position as the communicator. Fear arousing can produce the effect of communicants thinking they want to avoid it so as not to get bad like the video exemplified. The payoff technique shows the communicant knows the benefits that can be obtained by implementing the offered solution, namely religious moderation. The arrangement technique can be used to attract the attention of the communicant emotionally, by arranging sentences so that the communicant can understand it logically, and answering the doubts they have.